Moderate Exercise Training Combined With a High-Fat and Sucrose Diet Protects Pancreatic Islet Function in Male C57BL/6J Mice - Katherine Veras (Frontiers in Endocrinology, 2022)
Obesity is mainly caused by excess energy intake and physical inactivity, and the number of overweight/obese individuals has been steadily increasing for decades. Previous studies showed that rodents fed westernized diets exhibit endocrine pancreas deterioration and a range of metabolic disorders. This study evaluated the effects of moderated aerobic treadmill exercise training on pancreatic islet cell viability and function in mice consuming a high-fat and sucrose diet. In the present study, 60-day-old male C57BL/6J mice were divided into four groups: control (C), fed a standard diet AIN-93M (3.83 kcal/g; 70% carbohydrate (cornstarch and dextrinized starch were chosen as the major source of carbohydrate for the AIN-93 diet. In addition, a small amount of sucrose), 20% protein (casein), and 10% fat (soybean) with no training (i.e., sedentary); C + training (CTR, fed the standard diet with eight weeks of exercise; high-fat diet + sucrose (HFDS), fed a high fat and sucrose diet (5.2 kcal/g; 20% carbohydrate (cornstarch and dextrinized starch were chosen as the major source of carbohydrate), 20% protein (casein), 60% fat (Lard was chosen as the major source of fat and a small amount of soybean) + 20% sucrose diluted in drinking water with no training; and HFDS + training (HFDSTR). After eight weeks, the HFDS mice displayed increased body weight (P<0.001) and epididymal, inguinal and retroperitoneal adipose tissue mass (P<0.01). These mice also presented insulin resistance (P<0.01), glucose intolerance (P<0.001), impaired glucose-stimulated insulin secretion (GSIS) and were less responsive to the physiological net ROS production induced by glucose stimulus. The HFDS group’s pancreatic islet cells were 38% less viable and 59% more apoptotic than those from the C group (P<0.05). The HFDSTR improved glucose tolerance, body mass, insulin sensitivity and GSIS (P<0.05). Furthermore, HFDSTR mice had 53% more viable isolated pancreatic islets cells and 29% fewer apoptotic cells than the HFDS group (P<0.01). Thus, exercise training may slow down and/or prevent adverse metabolic effects associated with consuming a westernized diet.